THE EFFECT OF MERRY RIANA YOUTUBE CHANNEL ON THE EPISODE “SMARTNESS ALONE IS NOT ENOUGH FOR YOU TO BE SUCCESSFUL” ON STUDENT LEARNING MOTIVATION - Endah Purwitasari; Ardiya Putra Mahardika; Fitri Dwi Lestari (Universitas Gunadarma, 2022)
The development of this technology eventually led to a more creative audio-visual era. The era of social media that is increasingly dominant makes the needs of users or internet users meet their information needs and search for information to satisfy these needs, which can be obtained and fulfilled audio and visually through YouTube. Content creators have the opportunity to be able to attract audience segmentation with lots of videos uploaded on their YouTube channel accounts. This study aims to determine how much influence Merry Riana's YouTube channel shows on the episode